A conceptualisation of equitable social work practice with transgender and gender diverse communities. (26th November 2021) - Kia, Hannah; Göncü, Kaan; Nation, Kelendria; Gray, Jodi; Usher, Darren
Abstract: Although the experiences of transgender and gender diverse (TGD) people are increasingly recognised as relevant sites of inquiry in social work scholarship, empirically substantiated insights on equitable approaches to social work practice with TGD communities remain scant. In this qualitative study, we draw on semi-structured virtual interviews with TGD social service users in a Canadian province ( n  = 20), along with social workers in the same jurisdiction ( n  = 10), to generate knowledge on equitable social work practice with TGD populations. We rely on critical ecosystemic and intersectional lenses as guiding theoretical frameworks, together with constructivist approaches to grounded theory, to inform our analytical process. Our findings highlight that equitable social work practice with TGD communities may involve the following constituents: (1) accounting for social and historical context; (2) practising allyship by way of humility and reflexivity; (3) challenging cisnormativity interpersonally and organisationally and (4) promoting structural measures of trans inclusion to transform social work and social services. Drawing on our findings, we call on social work scholars, educators and practitioners to adopt various reflexive, relational, organisational and structural measures that promise to enhance social work's contribution to greater equity and social justice for TGD communities. Abstract : Transgender (trans) and gender diverse (TGD) people are individuals who, either fully or in part, do not identify with the sex they were assigned at birth. Despite growing understanding of the barriers that TGD people experience in accessing social services, research on the components of equitable social work practice with this population remains scant. Drawing on interviews with twenty TGD social service users and ten social workers, we discuss the perspectives of these participants on equitable practice and use their accounts to develop a framework for social work with TGD populations. We highlight the need for practice that is attentive to the social and historical context of TGD people in social services, is centred on building allyship with TGD communities and includes TGD people through specific interpersonal and organisational practices. We also explore the need for systemic measures that improve the representation of TGD people in social work and social services.